Hypoxia-inducible nuclear factors bind to an enhancer element located 3' to the human erythropoietin gene. - Semenza, G L (1991)
Human erythropoietin gene expression in liver and kidney is inducible by anemia or hypoxia. DNase I-hypersensitive sites were identified 3' to the human erythropoietin gene in liver nuclei. A 256-base-pair region of 3' flanking sequence was shown by DNase I protection and electrophoretic mobility-shift assays to bind four or more different nuclear factors, at least two of which are induced by anemia in both liver and kidney, and the region functioned as a hypoxia-inducible enhancer in transient expression assays. These results provide insight into the molecular basis for the regulation of gene expression by a fundamental physiologic stimulus, hypoxia.